Dampak Sosial Program PKH dan PBI BPJS pada Penerima Bantuan: Perspektif Masyarakat - Purba, Rachel Yohana Vatreciya; Maharani, Aisya; Harahap, Karina Olivia Pricila; Berlianti, Berlianti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to analyze the social impact of the Family Hope Program (PKH) and BPJS Contribution Assistance Recipients (PBI) from a community perspective. The approach used in this study is qualitative with an in-depth interview method with program beneficiaries to measure changes in social welfare. The results of the study indicate that PKH contributes to improving the ability to fulfill basic needs, children's education, and health services. BPJS PBI opens wider access to health services for vulnerable groups. However, several challenges were found, including the distribution of assistance that was not on target, social stigma against beneficiaries, and the quality of services that were still partly inadequate. In addition, this program also has an impact on increasing social participation in the community, such as involvement in beneficiary meetings (KPM) which strengthen community solidarity. Thus, the PKH and BPJS PBI programs have great potential to reduce social inequality in a sustainable manner.